GERAKAN NII DI BABAKAN CIPARI DAN EMPAT PILAR KEBANGSAAN - AKMAL SALIM RUHANA (Jurnal Dialog, 2017)
This research was aimed to elaborate the profile of NII (Negara Islam Indonesia/ Indonesian Islamic State) movement in Babakan Cipari, Garut, and to scrutinize its views on Panca¬sila, UUD 1945 (Indonesian constitution), Bhinneka Tunggal Ika (unity in diversity), and NKRI (Republic of Indonesia). In Indonesia NII has been one of controversial Islamic movement organizations from the Indonesian independence movement until today. Therefore, this research is interesting by showing the uniqueness of NII movement in Babakan Cipari as another variant of DI/NII movements, with some unique characteristics on religious thoughts and activities. In their perspectives, Pancasila and Bhinneka Tunggal Ika are tolerable, while UUD 1945 (amendment) and NKRI are problematic and unacceptable. Enriched by interviews with some key-informant, this research was written based on a descriptive-analytic method with a qualitative approach.